Risk Factors, Diagnosis, Management, and Outcome of Splanchnic Vein Thrombosis: A Retrospective Analysis - Derman, Benjamin A.; Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2015)
Objectives This study aims to determine the risk factors, diagnostic methods employed, treatment modalities, and outcome in patients with splanchnic vein thrombosis (SVT).Methods A retrospective chart review of patients, age 18 to 90 years, diagnosed with SVT at a single institution from January 1, 2010 to November 10, 2012. They were grouped as portal vein thrombosis (PVT)—including those combined with splenic vein thrombosis (SPVT) or mesenteric vein thrombosis (MVT)—and Budd–Chiari syndrome (BCS).Results Overall 246 SVT patients were identified, including 225 PVT and 21 BCS. Risk factors were liver disease, upper abdominal (regional) cancer and surgery, pancreatitis, and hereditary thrombophilia. The most common symptom was abdominal pain and most patients had abnormal liver function. Among those tested, the JAK2 V617F mutation was present in only 20% of the patients with PVT and 14% of the patients with BCS. Most patients were diagnosed by computed tomography. Anticoagulants were given to 30% of the patients with PVT and to 60% of the patients with BCS, with recurrence of SVT in 15% of the patients with PVT and 24% of the patients with BCS, regardless of anticoagulation.Conclusion As compared with published literature on SVT, we found a higher incidence of regional cancer and surgery and a lower incidence of the JAK2 V617F mutation.
Keywords: Budd–Chiari syndrome; mesenteric veins; portal vein; splenic vein; hepatic vein